0373 Blacks with Obstructive Sleep Apnea Report Greater Nighttime Insomnia Symptoms than Whites, but Don't Endorse Daytime Impairment. (27th May 2020) - Williams, N J; Butler, M; Roseus, J; Barnes, A; Blanc, J; Bubu, O M; Ebben, M; Grandner, M A; Krieger, A C; Jean-Louis, G; Perlis, M
Abstract: Introduction: Few studies have assessed insomnia severity in racial/ethnic minority patients with OSA. In recognition of the burden of OSA in blacks compared to whites, the current study sought to examine insomnia symptoms in a sample of black and white patients newly diagnosed with OSA, prior to treatment, at 3 and 6 months. Methods: 94 patients newly diagnosed with OSA provided demographics (age, sex, race/ethnicity), socioeconomic status, and completed the well-known and validated Insomnia Severity Index (ISI). To assess insomnia complaints, we ascertained total ISI score, nighttime sleep complaints, and daytime impairment. Linear regression and repeated measures analysis were conducted. Results: Mean age was 57.43 years ± 13.55; 63.8% were men and 35% were black. Mean BMI was 32.35 ± 7.04and 35% were diagnosed with hypertension. The mean ISI score for the total sample was 13.06 ± 7.06. The total ISI was significantly higher in blacks than whites, respectively (M=15.00 ± 7.17; M=12.02 ± 6.83, p<0.05) indicating moderate clinical insomnia in blacks, but not whites. In covariate-adjusted linear regression, nighttime complaints were statistically more pronounced in blacks ( b =1.71, SE=0.82, p<0.05) and women ( b =2.05, SE=0.72, p<0.01). There were no significant racial/ethnic differences with daytime impairment, but gender differences in daytime impairment remained ( b =2.93, SE=1.04 p<0.01). Results from repeated measures effects of race over time revealed that blacks had higher nighttime complaints across all time-points ( b =2.51, SE=1.10, p<0.05), but we did not observe a race-by-time interaction effect ( b =-0.89, SE=0.50). Conclusion: For the first time, we observed that overall ISI score and nighttime complaints are more pronounced in blacks than whites. Notably, only women endorsed complaints of daytime impairment. Findings from the study may contribute to understanding who will need treatment for relief of insomnia complaints. Support: K23HL125939